2018
DOI: 10.1186/s13104-018-3593-1
|View full text |Cite
|
Sign up to set email alerts
|

Cranial neural tube defect after trimethoprim exposure

Abstract: ObjectivesThe Neural Tube Defects Research Group of University of Malaya was approached to analyze a tablet named TELSE, which may have resulted in a baby born with central nervous system malformation at the University of Malaya Medical Centre. In this animal experimental study, we investigated the content of TELSE and exposure of its contents that resulted in failure of primary neurulation.ResultsLiquid Chromatography Tandem Mass spectrophotometry analysis of the TELSE tablet confirmed the presence of trimeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In 70-90% of cases abnormalities of corpus callosum such as hypoplasia or aplasia of the rostrum are presented. In closed spina bifida, the neural tube defect is covered with skin, there is no loss of cerebrospinal fluid, and cranial anatomy is normal [1,13,29].…”
Section: Discussionmentioning
confidence: 99%
“…In 70-90% of cases abnormalities of corpus callosum such as hypoplasia or aplasia of the rostrum are presented. In closed spina bifida, the neural tube defect is covered with skin, there is no loss of cerebrospinal fluid, and cranial anatomy is normal [1,13,29].…”
Section: Discussionmentioning
confidence: 99%
“…NTDs are a type of multifactorial disease, the result of genetic and environmental factors (Abdullah et al, 2018). A large number of studies have shown that 20% of NTDs is caused by genetic factors and 80% by non-genetic factors, but up to now, no breakthrough has been made in the etiology and pathogenesis of NTDs (Wang, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The CNS develops from the neuroectoderm, in the third week of gestation, following its folding and subsequent formation of a tube-like structure (Neural tube). 1 The anterior (rostral) and posterior (caudal) end usually closes respectively by 21 and 28 days after conception, with the closure beginning in the middle and extending in cranial and caudal directions. 1 From the rostral part, the brain (forebrain, midbrain, and hindbrain) develops, while the caudal part forms the spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…1 The anterior (rostral) and posterior (caudal) end usually closes respectively by 21 and 28 days after conception, with the closure beginning in the middle and extending in cranial and caudal directions. 1 From the rostral part, the brain (forebrain, midbrain, and hindbrain) develops, while the caudal part forms the spinal cord. 2 NTD may involve the whole length in a condition called posterior rachischisis, may remain open in the region of the brain because of the nonclosure of the anterior neuropore, resulting in a condition called anencephaly or the region of the spine (Spina bifida).…”
Section: Introductionmentioning
confidence: 99%